Biosorption OF Cu (II) by pretreated marina algae Grateloupia doryophora (Rhodophyta) - Rivera P., Jilver (2002)
Copper (11) adsorption properties of pre-treated biomass of marina algae Grateloupia doryophora (Rhodophyta) were investigated. The native biomass was treated with 0.2 M CaCl2, solution for 24 h under slow stirring. The solution pH was kept constant at pH = 5.0 using 0.1 M NaOH. The treated biomass was dried in an oven at 40ºC for 24 h. The adsorption capacity of the biomass strongly depends on equilibrium solution pH. At solution pH between 4 and 4,5 were observed the maximum adsorptive capacity of the pre-treated biomass.